Joining late, leaving early? Immigrant-native disparities in labor market exit - Olof Åslund; Fredrik Larsson; Lisa Laun (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
Theory and empirical findings on retirement determinants suggest that we may expect differences in labor market exit between native and foreign-born workers. Despite many countries seeing rising immigrant shares in their aging populations, alongside significant labor market disparities, the issue has so far received limited attention. Population-wide administrative data for Sweden show that the hazard rate to retirement is greater among immigrants already from age 50. But approaching age 65, especially marginal migrant groups have a stronger tendency to remain in the labor force and thus not adhering to the norm of retiring at a specific age. Education and family situation explain little of the retirement gaps, whereas labor market history, health, and occupational allocations are important determinants. Immigrant-native retirement differences are greater among men than among women. Overall findings suggest economic necessity and/or opportunity rather than varying preferences as drivers of differentials.
Keywords: J68; J64; C93; 330; labor market exit; immigrants; retirement hazard